Oral health-related quality of life among 12-year-olds in northern norway and north-west Russia. - Koposova, Natalia V; Eriksen, Harald M; Widström, Eeva; Eisemann, Martin; Opravin, Alexander; Koposov, Roman A (Oral health and dental management, 2012)
This article is part of Natalia V. Koposova's doctoral thesis, available in Munin at http://hdl.handle.net/10037/5595 Aims: To assess self-perceived oral health-related quality of life (OHRQoL) in 12-year-olds living in two areas in the Barents region: North-West Russia (Arkhangelsk) and Northern Norway (Tromsø). Methods: Sampling was performed according to a stratified cluster design and consisted of 590 Russian and 264 Norwegian 12-year-olds and their parents. After written consent from their parents, 514 Russian (87% attendance) and 124 Norwegian (47% attendance) children entered the study. The study included clinical examination (children) and questionnaires (children and parents). Dental caries and the aesthetic dental appearance were recorded under field conditions. Self-reports on background variables and oral health-related quality of life questions (CPQ11-14) were completed in classroom settings by children and at home by parents. Results: OHRQoL was found to vary depending on country of origin, with higher scores of CPQ11-14 domains among 12-year-olds from Russia. OHRQoL was found to be associated with dental caries, with higher scores among 12-year-olds with caries. Inferior emotional and social well-being were established as having the strongest association with quality of life. Dental caries showed an independent effect on OHRQoL scores, but this effect disappeared when controlling for background variables, with country of origin, family economy, parental education and aesthetic appearance as the most influential (R²=0.14). Conclusions: Norwegian 12-year-olds had better oral health and OHRQoL than their Russian counterparts. The impact of dental caries on OHRQoL was weak and aesthetic dental appearance and socio-economic determinants were found to be more important, probably reflecting the great differences in the standards of living between Northern Norway and North-West Russia.